COVID-19 Vaccine Uptake, Sources of Information and Side Effects Reported by Pregnant Women in Western Australia: Cross-Sectional Cohort Survey - Nicole Catalano; Shailender Mehta (JMIR Pediatrics and Parenting)
Abstract BackgroundPregnant women are a priority group for COVID-19 vaccination due to their vulnerability as a high-risk cohort. However, the currentCOVID-19 vaccine uptake rate for COVID-19 vaccination among pregnant women in Western Australia remains largely unknown. ObjectiveThis study aimed to explore pregnant women’s vaccination uptake rates, information sources, and experiences regarding COVID-19 vaccination during pregnancy. We hypothesized that uptake of vaccination among pregnant women is higher than indicated in previous studies, given differences in disease burden and public health restrictions at the time when data was collected. MethodsA cross-sectional survey was administered electronically to maternity patients at a single tertiary metropolitan hospital in Perth, Western Australia. ResultsA total of 520 women participated in the study. Overall, the antenatal COVID-19 vaccination rate was 79% (n=398). Approximately, 51% (n=256) of the women felt well-informed about the vaccine, and information was sourced primarily from their general practitioner (n=301, 60%), midwives (n=174, 35%), and obstetric doctors (n=64, 13%). Compared to Caucasian women, those of non-Caucasian ethnicity (n=332, 66% vs n=170, 34%; PP ConclusionsThe COVID-19 vaccine uptake among pregnant women was encouragingly high in our study, with favorable attitudes and acceptance for the vaccine observed in the majority of pregnant women. This self-reported study also identified opportunities for enhanced cultural competence and further education and training for hospital staff regarding COVID-19 vaccine information provision to ethnically diverse women. Further studies examining such interventions are warranted.